Ekuitas Merek dan Keputusan Pembelian: Studi Pada Konsumen Anak Usia Sekolah Dasar di Kota Depok - Endah Meiria (Esensi: Jurnal Bisnis dan Manajemen, 2017)
Brand Equity and Purchase Decision: Study at Elementary School Consumer in Depok CityThis study aims to identify: how brand equity’s factors of Biskuat and purchase decision of this biscuit by children consumer at the elementary school age in Depok City, as well as how the influence of brand equity’s factors of Biskuat towards purchase decision of this biscuit by children consumer at the elementary school age in Depok City. The object of this study is brand awareness, brand association, perceived quality, brand loyalty and purchase decision. The study was conducted in six sub-district of Depok City, with 100 children as the respondent from several schools and environments in six sub-district of Depok City.Testing hypotheses using path analysis (path analysis) which is equipped with testing the validity and reliability. Based on the analysis of the model lines of research, obtained results that brand equity which is brand awareness, brand association, perceived quality, and brand loyalty in partially and simultaneously has significantly affect to purchase decision.DOI:  10.15408/ess.v7i1.4783